191k views
5 votes
Solve for u. 3(3u-5)=39 .Simplify your answer as much as possible.

2 Answers

3 votes

3(3u-5)=39

Mutiply the bracket by 3

(3)(3u)(3)(-5)= 39

9u-15=39

Move -15 to the other side

Sign changes from -15 to +15

9u-15+15= 39+15

9u= 54

Divide by 9

9u/9= 54/9

Cross out 9 and 9, divide by 9 and then becomes u.

u= 6

Answer: u= 6

User Neena
by
5.4k points
6 votes

Explanation:

3(3u-5)=39

9u - 15 = 39

9u = 15 + 39

9u = 54

divide both by 9

u = 54/9

u = 6

User Sabir Al Fateh
by
5.8k points